A chromosome‐level genome of Antechinus flavipes provides a reference for an Australian marsupial genus with male death after mating. (21st September 2021) - Tian, Ran; Han, Kai; Geng, Yuepan; Yang, Chen; Shi, Chengcheng; Thomas, Patrick B.; Pearce, Coral; Moffatt, Kate; Ma, Siming; Xu, Shixia; Yang, Guang; Zhou, Xuming; et al.
Abstract: The 15 species of small carnivorous marsupials that comprise the genus Antechinus exhibit semelparity, a rare life‐history strategy in mammals where synchronized death occurs after one breeding season. Antechinus males, but not females, age rapidly (demonstrate organismal senescence) during the breeding season and show promise as new animal models of ageing. Some antechinus species are also threatened or endangered. Here, we report a chromosome‐level genome of a male yellow‐footed antechinus Antechinus flavipes . The genome assembly has a total length of 3.2 Gb with a contig N50 of 51.8 Mb and a scaffold N50 of 636.7 Mb. We anchored and oriented 99.7% of the assembly on seven pseudochromosomes and found that repetitive DNA sequences occupy 51.8% of the genome. Draft genome assemblies of three related species in the subfamily Phascogalinae, two additional antechinus species ( Antechinus argentus and A .  arktos ) and the iteroparous sister species Murexia melanurus, were also generated. Preliminary demographic analysis supports the hypothesis that climate change during the Pleistocene isolated species in Phascogalinae and shaped their population size. A transcriptomic profile across the A .  flavipes breeding season allowed us to identify genes associated with aspects of the male die‐off. The chromosome‐level A .  flavipes genome provides a steppingstone to understanding an enigmatic life‐history strategy and a resource to assist the conservation of antechinuses.